Proteins from Avastin® (bevacizumab) show tyrosine nitrations for which the consequences are completely unclear. - Jia Wan (Public Library of Science (PLoS), 2012)
Avastin® (bevacizumab) is a protein drug widely used for cancer treatment although its further use is questionable due to serious side effects reported. As no systematic proteomic study on posttranslational modifications (PTMs) was reported so far, it was the aim of the current study to use a gel-based proteomics method for determination of Avastin®-protein(s). Avastin® was run on two-dimensional gel electrophoresis (2-DE), spots were picked, followed by multi-enzyme in-gel digestion. Subsequently, the resulting peptides and posttranslational modifications were identified by mass spectrometry (nano-LC-ESI-MS/MS; HCT and LTQ Orbitrap MS). Heavy and light chains were observed and the 9 spots that were picked from 2DE-gels were identified as bevacizumab with high sequence coverage. MS/MS results showed multiple tyrosine nitrations on the Avastin® light and heavy chains that were either represented as nitrotyrosine or as aminotyrosine, which was shown to be generated from nitrotyrosine under reducing conditions. Protein nitration is known to significantly change protein functions and interactions and it may well be that some of the adverse effects of the protein drug Avastin® may be due to this PTM, which may have been generated during production--thus, nitration of Avastin® is a challenge for the pharmaceutical industry.